Selective Regulation of GluA Subunit Synthesis and AMPA Receptor-Mediated Synaptic Function and Plasticity by the Translation Repressor 4E-BP2 in Hippocampal Pyramidal Cells - Ran, Israeli (J Neurosci, 2013)
The eukaryotic initiation factor 4E-binding protein-2 (4E-BP2) is a repressor of cap-dependent mRNA translation and a major downstream effector of the mammalian target of rapamycin (mTOR) implicated in hippocampal long-term synaptic plasticity and memory. Yet, synaptic mechanisms regulated by 4E-BP2 translational repression remain unknown. Combining knock-out mice, whole-cell recordings, spine analysis, and translation profiling, we found that 4E-BP2 deletion selectively upregulated synthesis of glutamate receptor subunits GluA1 and GluA2, facilitating AMPA receptor (AMPAR)-mediated synaptic transmission and affecting translation-dependent chemically induced late long-term potentiation (cL-LTP). In 4E-BP2 knock-out (4E-BP2(−/−)) mice, evoked and miniature EPSCs were increased, an effect mimicked by short-hairpin RNA knockdown of 4E-BP2 in wild-type mice, indicating that 4E-BP2 level regulates basal transmission at mature hippocampal AMPAR-containing synapses. Remarkably, in 4E-BP2(−/−) mice, the AMPA to NMDA receptor (NMDAR) EPSC ratio was increased, without affecting NMDAR-mediated EPSCs. The enhanced AMPAR function concurred with increased spine density and decreased length resulting from greater proportion of regular spines and less filopodia in 4E-BP2(−/−) mice. Polysome profiling revealed that translation of GluA1 and GluA2 subunits, but not GluN1 or GluN2A/B, was selectively increased in 4E-BP2(−/−) hippocampi, consistent with unaltered I–V relation of EPSCs mediated by GluA1/GluA2 heteromers. Finally, translation-dependent cL-LTP of unitary EPSCs was also affected in 4E-BP2(−/−) mice, lowering induction threshold and removing mTOR signaling requirement while impairing induction by normal stimulation. Thus, translational control through 4E-BP2 represents a unique mechanism for selective regulation of AMPAR synthesis, synaptic function, and long-term plasticity, important for hippocampal-dependent memory processes.